2017
DOI: 10.1159/000484930
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Helicobacter pylori Eradication Rates of 2-Week Levofloxacin-Containing Triple Therapy, Levofloxacin-Containing Bismuth Quadruple Therapy, and Standard Bismuth Quadruple Therapy as a First-Line Regimen

Abstract: i.d, levofloxacin 500 mg, once daily). The primary outcome was the eradication rate in the intention-to-treat (ITT) and per protocol (PP) analysis. Results: The eradication rates of the above 3 groups using ITT analysis were RBAL 83.8%, RBMT 88.3%, and RAL 74.8% compared with 91.2, 92.5, and 79.2%, respectively, using PP analysis. The eradication rate using RBMT was significantly higher than that of RAL (p = 0.029 in ITT analysis and p = 0.017 in PP analysis). Several side effects occurred in 156 patients (54.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Bismuth‐containing quadruple therapy could partially overcome antibiotic resistance. However, AEs occurred in more than 50% of the levofloxacin‐containing bismuth quadruple therapy and standard bismuth‐containing quadruple therapy, compared with 26.2% in triple therapy 22 . There were also many competing conditions when it came to the elderly or people with multiple diseases compared to younger ones, considering the possibility of interaction with concomitant medicines 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Bismuth‐containing quadruple therapy could partially overcome antibiotic resistance. However, AEs occurred in more than 50% of the levofloxacin‐containing bismuth quadruple therapy and standard bismuth‐containing quadruple therapy, compared with 26.2% in triple therapy 22 . There were also many competing conditions when it came to the elderly or people with multiple diseases compared to younger ones, considering the possibility of interaction with concomitant medicines 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…With the reference to the prevalence of primary fluoroquinolone resistance is higher than 15% in Asia (China, Iran, Japan, Pakistan) and Russia, bismuth subsalicylate was added to the combination in our study (23). Kahramanoğlu et al (24) also found that a 14-day levofloxacin-containing BQT was somewhat more efficient than levofloxacin-containing triple therapy. Although the MBCT regimes had the highest compliance, both the 10day and 14-day MBCT protocols were a lower eradication rate than BQT regimens in our study.…”
Section: Discussionmentioning
confidence: 68%
“…50 A comparison of levofloxacin-containing triple therapy with levofloxacin-containing BQT and standard BQT from Turkey found bismuth-containing regimens to be superior. 51 An American study found modified dual therapy consisting of higher doses of PPI reached comparative eradication rates with BQT, without significant adverse effects. 52…”
Section: B Is Muthmentioning
confidence: 99%